The impact of foreign direct investment on income inequality in Vietnam: A spatial regression approach - Ho, Thuy Tien; Trinh, Thi Lien (Journal of Finance - Marketing Research, 2025)
Vietnam has experienced strong growth in foreign direct investment; however, income inequality remains at a high level. Therefore, this study utilizes data from 63 provinces and cities in Vietnam over the period 2010 – 2023 and employs a spatial regression model to analyze the impact of foreign direct investment and socio-economic factors on income inequality. The results indicate that foreign direct investment, population, domestic private investment, and public investment are negatively correlated with income inequality, while unemployment rate, institutional quality, and public expenditure contribute to increased income inequality. Urbanization rate and technological capacity show no significant impact. The study recommends directing foreign direct investment towards poorer regions and labor-intensive sectors, as well as strengthening vocational training. Policies for attracting and utilizing foreign direct investment should be designed to promote inclusive growth and reduce income disparities across regions.